Subaltern Testimony and Necropolitical Sovereignty in Shadia al-Zoubi’s Aradna al-Hurriyyah': Shahadat al-Tabi‘ wa al-Siyadah al-Nikrusiyasiyyah fi “Aradna al-Hurriyyah” li-Shadiyah al-Zu‘bi - Ahmad Fauzi Simatupang; Achmad Syafri Maulana (An-Nahdah Al-'Arabiyah, 2026)
This study examines Aradna al-Hurriyah by Shadia al-Zoubi from a postcolonial perspective by employing Gayatri Chakravorty Spivak's theory of Subalternity and Achille Mbembe's concept of Necropolitics. It aims to investigate the mechanisms of oppressive sovereignty in Syria and the forms of resistance articulated by subaltern subjects within testimonial literature. The study adopts a descriptive qualitative method, utilizing close reading and qualitative content analysis. The primary data consist of narratives, phrases, and linguistic expressions that represent violence, dehumanization, and freedom in the text. The findings reveal that the Syrian regime exercises internal colonialism through indiscriminate shootings, the bombing of civilian infrastructure, arbitrary detention, and the use of chemical weapons as instruments of necropolitical control. The analysis further demonstrates that testimonial narrative not only represents the lived experiences of subaltern suffering but also constitutes a space of political articulation through which silenced subjects are transformed into agents capable of renegotiating relations of power under conditions of state violence. These findings extend existing scholarship on Syrian testimonial literature by demonstrating the interconnection between subaltern experience, necropolitical governance, and the reconstruction of identity within a unified postcolonial analytical framework. Consequently, this study argues that testimonial literature functions not merely as a representation of wartime suffering but also as a medium for restoring human dignity, collective memory, and the sovereignty of identity while serving as a form of resistance to oppressive power.   تتناول هذه الدراسة رواية "أردنا الحرية"  للكاتبة شادية الزعبي من منظور ما بعد الاستعمار، مستندةً إلى نظرية التابع (Subalternity) عند غاياتري تشاكرافورتي سبيفاك ومفهوم السياسات الموتية (Necropolitics) لدى أشيل مبيمبي. وتهدف إلى الكشف عن آليات السيادة القمعية في سوريا، وأشكال المقاومة التي يعبر عنها التابعون في أدب الشهادة. واعتمدت الدراسة المنهج الوصفي النوعي من خلال القراءة الدقيقة (Close Reading) وتحليل المحتوى الكيفي. وتمثلت البيانات الرئيسة في السرديات والعبارات والتعبيرات اللغوية التي تمثل العنف ونزع الإنسانية والحرية داخل النص. وأظهرت النتائج أن النظام السوري يمارس شكلاً من أشكال الاستعمار الداخلي عبر إطلاق النار العشوائي، وقصف البنية التحتية المدنية، والاعتقال التعسفي، واستخدام الأسلحة الكيميائية بوصفها أدوات للسيطرة السياسات الموتية. كما بين التحليل أن السرد الشهادي لا يقتصر على تمثيل معاناة التابعين، بل يشكل فضاءً للتعبير السياسي تتحول فيه الذوات المهمشة والمقموعـة إلى فواعل قادرة على إعادة التفاوض بشأن علاقات السلطة في ظل عنف الدولة. وتسهم هذه النتائج في توسيع آفاق دراسة الأدب الشهادي السوري من خلال إبراز الترابط بين تجربة التابع، وآليات السياسات الموتية، وإعادة تشكل الهوية ضمن إطار تحليلي موحد يستند إلى دراسات ما بعد الاستعمار. وتخلص الدراسة إلى أن أدب الشهادة لا يؤدي وظيفة تمثيل معاناة ضحايا الحرب فحسب، بل يشكل أيضاً وسيلة لاستعادة الكرامة الإنسانية، والذاكرة الجمعية، وسيادة الهوية، فضلاً عن كونه ممارسةً مقاومةً في مواجهة السلطة القمعية.   Penelitian ini mengkaji Aradna al-Hurriyah karya Shadia al-Zoubi melalui perspektif poskolonial dengan menggunakan teori Subalternitas Gayatri Chakravorty Spivak dan konsep Nekropolitik Achille Mbembe. Penelitian ini bertujuan mengungkap mekanisme kedaulatan represif di Suriah serta bentuk-bentuk perlawanan yang diekspresikan oleh subjek subaltern dalam sastra kesaksian. Penelitian menggunakan metode deskriptif kualitatif dengan teknik close reading dan analisis isi kualitatif. Data primer berupa narasi, frasa, dan ungkapan linguistik yang merepresentasikan kekerasan, dehumanisasi, dan kebebasan dalam teks. Hasil penelitian menunjukkan bahwa rezim Suriah menjalankan praktik kolonialisme internal melalui penembakan membabi buta, pengeboman infrastruktur sipil, penahanan sewenang-wenang, serta penggunaan senjata kimia sebagai instrumen kontrol nekropolitik. Analisis juga memperlihatkan bahwa narasi kesaksian tidak hanya merepresentasikan pengalaman penderitaan subaltern, tetapi sekaligus membentuk ruang artikulasi politik yang mentransformasikan posisi subjek yang dibungkam menjadi agensi yang mampu menegosiasikan kembali relasi kuasa dalam konteks kekerasan negara. Temuan tersebut memperluas pembacaan terhadap sastra kesaksian Suriah dengan memperlihatkan keterkaitan antara pengalaman subaltern, mekanisme nekropolitik, dan proses rekonstruksi identitas dalam satu kerangka analisis poskolonial. Dengan demikian, penelitian ini menegaskan bahwa sastra kesaksian berfungsi sebagai medium restorasi martabat kemanusiaan, memori kolektif, dan kedaulatan identitas di tengah kekerasan serta represi sistemik.